Independent and Combined Influence of Homeownership, Occupation, Education, Income and Community Poverty on Physical Health in Persons with Arthritis - Callahan, Leigh F. (2011)
OBJECTIVE: To examine the independent and combined influence of individual and community-level socioeconomic (SES) measures with physical health status outcomes in people with self-reported arthritis. METHODS: From 2004-2005, 968 participants completed a telephone survey assessing health status, chronic conditions, community characteristics, and socio-demographic variables. Individual-level SES measures: homeownership, occupation [professional, or not], educational attainment (< high school (HS), HS degree, and > HS), income (<15, 15-45, >$45K) and community poverty: 2000 U.S. Census block-group “% of individuals living below the poverty line” (low, medium, high) were used. Outcomes were physical functioning (MOS SF-12v2 PCS), functional disability (HAQ) and the CDC HRQOL Healthy Days physical and limited activity days and were analyzed via multivariable regressions. RESULTS: When entered separately, all individual-level SES variables were significantly (p<0.01) associated with poorer PCS, HAQ, and CDC HRQOL scores. A higher magnitude of effect was seen for household income, specifically <$15,000 in final models with all 4 individual SES measures and community poverty. The magnitude of effect for education is reduced and marginally significant for PCS and number of physically unhealthy days. No effects were seen for occupation, homeownership, and community poverty. CONCLUSIONS: Findings confirm that after adjusting for important covariates, lower individual and community-level SES are associated with poorer physical health outcomes, while household income is the strongest predictor (as measured by both significance and effect) of poorer health status in final models. Studies not having participant-reported income available should make use of other SES measures as they do independently predict physical health.